Removal of Methylene Blue by Red Macro Alga Euchema Spinosum Sp.: Pretreatment and Desorption Assessment - Mokhtar, Nadiah; A.Aziz, Edriyana; Aris, Azmi; W.Ishak, W.F.; Abdul Halim, Hasmanie; Johari, Najiha; N.Moni, Syazwan (International Journal of Engineering and Technology, 2018)
Red algae species, Euchema Spinosum (ES) in Malaysia possesses excellent biosorbent properties in removing dyes from aqueous solutions. Studies had been made on the effect of pretreatment and reusability of this species as a biosorbent for economic viability. In the present study, physical and chemical pretreatments processes were employed on the ES. Desorption using seven different eluents (hydrochloric acid (HCl), sodium hydroxide (NaOH), phosphoric acid (H3PO4), potassium hydroxide (KOH), sodium chloride (NaCl), nitric acid (HNO3 and deionized water).Â Caharacterization of ES biosorbent was conducted using FTIR to investigate the active functional group responsible in the biosorption process. It was observed that the pretreatment process does not enhance the uptake capacity of ES.Â Among of the six eluents used, it is suggested HNO3 as an effective eluent with 51% desorption efficiency.Â Â Through regeneration study, HNO3 as eluent can promote four times of biosorption-desorption cycles. FTIR confirm the functional groups such as â€“OH, â€“NH and â€“COO- are responsible for the MB dye biosorption. The experiment displays that the ES does not require any pretreatment procedure to improve biosorption efficiency and has the capability of regeneration hence suggesting that ES is indeed an economical biosorptive material for MB dye removal.